Analyze the Effect of First Media Service Quality Towards Consumer Satisfaction Using the ServQual Method - Rezi, Maulana; Chandra, Gilang; Budiman, Satiadji; Putra, Gandy; Rizki, Arighi (Universitas Malikussaleh, 2019)
First Media is one of the companies in the field of recording technology that provides internet network services. To find out the value of the influence of first-class operators on consumer satisfaction in this study used the associative method. Descriptive method to determine the level of buyer satisfaction with the operator. This study used a questionnaire distributed to 100 consumers. The results showed that consumers who were very satisfied with the quality of service were as many as 39 people. Satisfied consumers are as many as 13 people, and consumers who feel dissatisfied are as many as 48 people. From the results of easy linear regression the miles are considered that the regression equation is Y = -0.018 + 0.051X, which means the constant (β0) is -0.018 shows that when the service quality variable does not change, the average customer satisfaction (Y) is -0.018. Service quality regression coefficient of 0.051. This shows that every one constant increase in service quality variables will increase customer satisfaction (Y) by 0.051. Positive regression coefficient, this shows the higher the first-class operator, the higher the customer satisfaction (Y). From the calculation of R2 termination coefficient, it is known that service quality has an influence of 50.5% on customer satisfaction.